A new species of Ampithoe Leach, 1814 (Senticaudata, Ampithoidae) from Brazilian coast - Correia, Filipe R.; Guedes-Silva, Elkênita; Souza-Filho, Jesser F. (Zootaxa, 2016)
In this paper we describe a new species from Brazilian waters, Ampithoe suapensis sp. nov., from Pernambuco State, Brazil. This species is readily separated from its congeners by the following states of characters: mandible with palp slender, with 2 long setae on distal margin of article 3; gnathopod 2 propodus oval with palm densely setose, extremely acute and lacking ornamentation, peduncle of male uropod 1 with a blunt interramal process. Also, a key for the Ampithoe species found in Brazilian waters is provided.